Soil Microbial Community Response to Nitrogen Application on a Swamp Meadow in the Arid Region of Central Asia - Hu, Yang; Chen, Mo; Yang, Zailei; Cong, Mengfei; Zhu, Xinping; Jia, Hongtao (Frontiers in Microbiology, 2022)
Although a large number of studies have reported the importance of microbial communities in terrestrial ecosystems and their response to nitrogen (N) application, it is not clear in arid alpine wetlands, and the mechanisms involved need to be clarified. Therefore, the response of the soil microbial community in a swamp meadow to short-term (1 year) N application (CK: 0, N1: 8, N2: 16 kg·N·hm−2·a−1) was studied using 16/18S rDNA high-throughput sequencing technology. Results showed that N application had no significant effect on soil microbial community diversity, but significantly changed soil bacterial community structure. N1 and N2 treatments significantly reduced the relative abundance of Chloroflexi (18.11% and 32.99% lower than CK, respectively). N2 treatment significantly reduced the relative abundance of Nitrospirae (24.94% lower than CK). Meanwhile, N application reduced the potential function of partial nitrogen (N) and sulfur (S) cycling in bacterial community. For example, compared with CK, nitrate respiration and nitrogen respiration decreased by 35.78%-69.06%, and dark sulfide oxidation decreased by 76.36%-94.29%. N application had little effect on fungal community structure and function. In general, short-term N application directly affected bacterial community structure and indirectly affected bacterial community structure and function through available potassium (K), while soil organic carbon (SOC) was an important factor affecting fungal community structure and function.